A new species of Habenaria (Orchidaceae, Orchidoideae, Orchideae) from Yunnan, China - Lin, Dongliang; Qin, Shiyu; Jin, Xiaohua (Phytotaxa, 2024)
A new species of Orchidaceae, Habenaria tiechangensis, from Yunnan province is described and illustrated based on morphological characters and molecular phylogenetic analysis. The results indicated that it belongs to H. josephi group and is similar to H. diplonema but differs from the latter by having short and lanceolate lateral lobes of lip and a pair of distinctive horn-like stigmas.